Law and justice as seen on TV - Rapping, Elayne (New York Univ. Press, 2003)
1. The return of the attorney-hero: politics and justice in the prime time courtroom -- 2. Aliens, nomads, mad dogs, and road warriors: tabloid TV and new face of criminal violence -- 3. Signs of the times: "OZ" and the sudden visibility of prisons on television -- 4. Cameras, court TV, and the rise of the criminal trial as major media event -- 5. The politics of representation: gender, violence, and criminal justice -- 6. Television and family dysfunction: from the talk show to the courtroom -- 7. Television and the demonization of youth -- 8. Television, melodrama, and the rise of the victims' rights movement